Kanyashree Prakalpa in West Bengal Desirability and Promises - Mukherjee, Soumi; Mukherjee, Subrata (JOURNAL OF INDIAN EDUCATION, 2020)
Girls’ education in West Bengal is neither constrained by poor physical access to schools nor by high school fees, especially in government and government aided schools. This paper attempts to understand the need for conditional cash transfer programmes in education for girl students in West Bengal by using representative sample survey data. The paper compares Kanyashree Prakalpa (KP) with similar programmes in India and by using qualitative data, the paper tries to understand the interplay between educational progress and conditional cash transfers. The paper finds that KP is similar, in terms of conditions and transfers, to its predecessors like the Ladli scheme. Access to free education in West Bengal is easier compared to other states and data shows that most educational expenditure is incurred on private tuitions. Noticeably, the KP targets girls’ dropout in a state where boys’ dropouts are higher. The state government’s emphasis on a demand side intervention like KP should not substitute its equally important role in addressing supply side issues in the school education sector.